Stress corrosion cracking initiation susceptibility of Alloy 182 with different surface treatments. (March 2022) - Que, Z.; Saario, T.; Toivonen, A.; Ehrnstén, U.
Abstract: The effects of machining surface preparations on the stress corrosion cracking (SCC) susceptibility in boiling water reactor environment were evaluated for Alloy 182 weld metal. Constant extension rate tensile test, constant load test and electrochemical tests (passivation, current-voltage curves and electrochemical impedance spectroscopy) showed that the surface treatments strongly influence the resistance to SCC initiation. The machining-induced deformation and surface oxide layer from the surface treatments affect the re-passivation behaviour and SCC initiation susceptibility. The SCC susceptibility of the studied surface treatments was found following the sequence of shot peened > industrial surface milled > polished > advanced manufactured surface. Highlights: SCC of Alloy 182 was evaluated with CERT, constant load and electrochemical tests. SCC resistance with surface treatments rank as: SAM > RS > STI > SP. Passivation, current-voltage and EIS tests show high corrosion rate of SP surface.